Kidney-specific lymphangiogenesis increases sodium excretion and lowers blood pressure in mice. Issue 5 (May 2020) - Balasubbramanian, Dakshnapriya; Baranwal, Gaurav; Clark, Mary-Catherine C.; Goodlett, Bethany L.; Mitchell, Brett M.; Rutkowski, Joseph M.
Abstract : Objective: Hypertension is associated with renal immune cell accumulation and sodium retention. Lymphatic vessels provide a route for immune cell trafficking and fluid clearance. Whether specifically increasing renal lymphatic density can treat established hypertension, and whether renal lymphatics are involved in mechanisms of blood pressure regulation remain undetermined. Here, we tested the hypothesis that augmenting renal lymphatic density can attenuate blood pressure in established hypertension. Methods: Transgenic mice with inducible kidney-specific overexpression of VEGF-D ('KidVD+' mice) and KidVD− controls were administered a nitric oxide synthase inhibitor, L-NAME, for 4 weeks, with doxycycline administration beginning at the end of week 1. To identify mechanisms by which renal lymphatics alter renal Na + handling, Na + excretion was examined in KidVD+ mice during acute and chronic salt loading conditions. Results: Renal VEGF-D induction for 3 weeks enhanced lymphatic density and significantly attenuated blood pressure in KidVD+ mice whereas KidVD− mice remained hypertensive. No differences were identified in renal immune cells, however, the urinary Na + excretion was increased significantly in KidVD+ mice. KidVD+ mice demonstrated normal basal sodium handling, but following chronic high salt loading, KidVD+ mice had a significantly lower blood pressure along with increased urinary fractional excretion of Na + . Mechanistically, KidVD+ mice demonstrated decreased renal abundance of total NCC and cleaved ENaCα Na + transporters, increased renal tissue fluid volume, and increased plasma ANP. Conclusion: Our findings demonstrate that therapeutically augmenting renal lymphatics increases natriuresis and reduces blood pressure under sodium retention conditions. Abstract : Supplemental Digital Content is available in the text